Risk Factors Leading to Extubation Failure in a Pediatric Intensive Care Unit: A Descriptive Study from a Tertiary Care Hospital in Pakistan: Risk Factors Leading to Extubation Failure in a Pediatric Intensive Care Unit - Rehman, Iqra; Abid, Madhia; Bai, Naila; Yousuf, Fareeha; Masqati, Noor Un Nisa; Aftab, Seema; Yahya, Yousuf (Pakistan Journal of Health Sciences, 2026)
Extubation failure (EF), defined as the need for reintubation within 72 hours of planned removal of mechanical ventilation, is a serious complication in pediatric intensive care units, yet local data from low- and middle-income countries are limited. Objectives: To describe clinical risk factors for EF among ventilated children in a tertiary Pediatric Intensive Care Unit (PICU) in Pakistan. Methods: This research conducted a six-month descriptive cross-sectional study in the PICU of Civil Hospital Karachi, enrolling all children under 12 years who received invasive mechanical ventilation for >12 hours and subsequently required reintubation within 72 hours of planned extubation. Demographic variables and predefined risk factors (hemodynamic instability, gas-exchange failure, airway obstruction, acute respiratory disease, chronic neurologic disease, malnutrition, poor cough reflex, and exposure to sedatives, inotropes, and steroids) were recorded on a standardized, validated proforma and analyzed using SPSS-23 with chi-square tests (p≤0.05). Results: Among 133 EF episodes, the most frequent risk factors were hemodynamic instability (24.8%), inotrope and steroid use (24.8% each), upper airway obstruction and hypoxemic respiratory failure (15% each), and poor cough reflex (15%), with several patients exhibiting multiple overlapping risk factors. Upper airway obstruction and poor cough reflex were more common in males, whereas cyanotic congenital heart disease and chronic neurologic conditions occurred exclusively in children >5 years of age. Conclusions: EF in this setting is multifactorial, dominated by hemodynamic instability, gas-exchange impairment, and airway-protective deficits; structured, age- and sex-aware extubation-readiness assessment focused on these risks may help reduce reintubation in resource-limited PICUs.